Genetics of inherited platelet disorders - Gothwal, M.; Sandrock-Lang, K.; Zieger, B. (Hämostaseologie, 2014)
The current review describes inherited platelet disorders, illustrates their clinical phenotype and molecular genetic defects. Platelets are the key molecules mediating haemostasis via adhesion, activation and clot formation at the site of injury. The inherited platelet disorders can be classified according to their platelet defects: receptor/cytoskeleton defects, secretion disorder, and signal transduction defect.Patients with inherited thrombocytopathia present with mucous membrane bleedings (epistaxis, gingival bleeding) and may present with serious life threatening bleedings following surgery or trauma. Therefore, biochemical and molecular genetic characterization of inherited platelet disorders is important to understand these disorders and to support an efficient therapy.
Keywords: Platelets; inherited platelet disorders; molecular genetics; bleeding disorder